Refueling and complex overhaul of the USS Nimitz (CVN 68) : lessons for the future - Schank, John F. (John Frederic), 1946-; Arena, Mark V.; Rushworth, Denis; Timson, F. S. (Frederick Samuel); Birkler, J. L., 1944-; Chiesa, James, 1949-; National Defense Research Institute (U.S.). Acquisition and Technology Policy Center; Rand Corporation; United States. Navy. (Santa Monica, CA : RAND, 2002)
The midlife refueling/complex overhaul (RCOH) of a nuclear aircraft carrier may be the most challenging engineering and industrial task undertaken anywhere by any organization. In addition to refueling the onboard reactor, a variety of maintenance and repair actions must also be undertaken, all while the entire ship is being modernized. The midlife refueling/complex overhaul (RCOH) of the USS Nimitz (CVN 68), completed in 2001, took five years of planning and three years of execution. This was the first RCOH for the Nimitz class and only the fourth ever accomplished on a nuclear aircraft carrier. Numerous budget and work-requirements changes and a four-month labor-union strike during the overhaul caused the scheduled completion of the project to slip by several months and resulted in significant cost growth. This report analyzes the planning and execution of the CVN 68 RCOH to identify changes in processes and procedures that could lead to better cost and schedule performance for the nine remaining Nimitz-class RCOHs. Many improvements in planning and execution have already been implemented for the CVN 69 and 70 RCOHs; based on our study findings, we suggest that the following three sets of additional actions be taken: (1) improve the planning process; (2) improve data and estimating capabilities; and (3) improve the relationship between the Navy and its carrier construction contractor, Newport News Shipbuilding, the only U.S. shipyard with the capability to build and refuel nuclear aircraft carriers.
Introduction -- Background -- Budgeting, Planning, and Contracting for the RCOH -- Cost Growth -- Assessing the Planning and Execution Processes -- Conclusions and Recommendations -- Appendix A: Chronology and Work Schedule -- Appendix B: The 1999 Strike Against Newport News Shipbuilding -- Appendix C: Commercial Analogs to the RCOH Process.
"National Defense Research Institute."
"The research ... was carried out within the Acquisition and Technology Policy Center of RAND's National Defense Research Institute"--Preface.
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Keywords: Nimitz (Ship : CVN-68); Marine nuclear reactor plants -- United States -- Maintenance and repair; Nuclear aircraft carriers -- United States -- Maintenance and repair